The diversity of trees species in Taman Wisata Alam Ruteng, East Nusa Tenggara - DEDE SETIADI (Society for Indonesian Biodiversity, 2005)
The objectives of this research were to know important value, diversity index, evenness index, and similarity index species of tree in Taman Wisata Alam of Ruteng. This research use Centered Quatered Method with transek longly is band follow the example of 200 m with parallel direction of contour. At entire all area specified by 7 station of perception that is station I area of Mocok with height 600 m asl, station II area of Ponggeok with height 750 m asl, station III area of Lempang Paji with height 900 m asl, station IV area of Uluwae with height 1050 m asl, station V area of Nggalakleleng 1200 m asl, station VI area of Gololalong with height 1350 m asl, and station VII area of Mano with height 1500 m asl. From result data analysis hence can be taken by some conclusion of the following: (i) In each height perceived by species having highest important value different each other. Species having high important value at entire all station of present is Elaeocarpus floribundus, Podocarpus amarus, Ehretia timorensis, Knema cinerea, Elaeocarpus sp., Prunus sp., and Litsea sp. (ii). Diversity index was between 0,98-1,51, the value enter in low category. (iii). Eveness index of species at entire all station of perception relative is of equal was between 0,847-1,020. (iv). According of similarity index at entire all station which compared of generally lowering. There are no combination of station of perception which compared yield value of similarity index at > 75%.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: diversity, trees, Taman Wisata Alam Ruteng, East Nusa Tenggara.